Star Wars. - Waid, Mark 1962- (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2015)
In the aftermath of the Rebel Alliance's victory, Princess Leia grapples with her loss as a new mission finds her in the underground world of Sullust.